STUDENT ACTIVITIES ON LEARNING CHEMISTRY - Cyndi Prasetya (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
This case study aims to analyze student activities and student responses to the chemistry learning process. This research was conducted at SMAN 8 Banda Aceh using a qualitative approach. Data collection methods used in the form of observation, interviews, surveys and documentation during the case study. The technique for selecting resource persons was adjusted based on the data to be obtained, the selected sources were vice principals, chemistry teachers and students. Data analysis technique uses descriptive qualitative. Based on the results of observations at SMAN 8 Banda Aceh classified as having adequate facilities, the activities of students in the second observation were classified as good and experienced an increase, namely 71.43%. The obstacles faced in learning chemistry based on interviews with teachers are that students are less motivated in learning, the lack of understanding of students about the importance of learning chemistry, there is limited time to do practicum.